International Day of asbestos victims: state of science, state of the world (Paris, 2014)
"This book contains the proceedings from the “International Day of Asbestos Victims” symposium organized by French National Association for the Defense of Asbestos Victims (ANDEVA) which was held in Paris on October, 12 2012. This two-part book includes presentations from “State of Science” and “State of the World."